Grid integration of electric vehicles in open electricity markets - Wu, Qiuwei (Chichester, West Sussex, United Kingdom : Wiley, 2013)
Presenting the policy drivers, benefits and challenges for grid integration of electric vehicles (EVs) in the open electricity market environment, this book provides a comprehensive overview of existing electricity markets and demonstrates how EVs are integrated into these different markets and power systems. Unlike other texts, this book analyses EV integration in parallel with electricity market design, showing the interaction between EVs and differing electricity markets. Future regulating power market and distribution system operator (DSO) market design is covered, with up-to-date.
Electrification of vehicles : policy drivers and impacts in two scenarios -- EVs and the current Nordic electricity market -- Electric vehicles in future market models -- Investments and operation in an integrated power and transport system -- Optimal charging of electric drive vehicles : a dynamic programming approach -- EV portfolio management -- Analysis of regulating power from EVs -- Frequency control reserves and voltage support from electric vehicles -- Operation and degradation aspects of EV batteries -- Day-ahead tariffs for congestion management from EVs -- Impact study of EV integration on distribution networks.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Electric automobiles -- Power supply -- Forecasting; Electric automobiles -- Power supply -- Economic aspects; Electric power-plants -- Load; Electric power consumption; Electric utilities; Electric automobiles -- Power supply -- Economic aspects; Electric automobiles -- Power supply -- Forecasting; Electric power consumption; Electric power plants -- Load; Electric utilities; TECHNOLOGY & ENGINEERING -- Power Resources -- Electrical; Electronic books; Electronic books